Aortic Arch Baroreceptor Stimulation in an Experimental Goat Model: A Novel Method to Lower Blood Pressure - Benson, Jacobus F.; Schoeman, Johan P.; Venter, Frans J.; Ker, James A.; Zeiler, Gareth E.; Bester, Lynette; van Niekerk, Janet; Tintinger, Gregory R. (Frontiers in Cardiovascular Medicine, 2019)
The effect of aortic baroreceptor stimulation on blood pressure manipulation was assessed using the goat species Capra aegagrus hircus. The aim of this study was to manipulate blood pressure with future intention to treat high blood pressure in humans. The ages of the animals ranged from six months to two years. A standard anaesthesia protocol was used. A lateral thoracotomy was performed to gain access to the aortic arch. Data was collected with the Vigileo system. Pre stimulation blood pressure was compared with maximum post stimulation blood pressure values. Results were analysed with the Wilcoxon signed rank test. In the study thirty eight animals were enrolled. Baroreceptor stimulation was performed for each animal using 3 different electrodes each of which emits an electrical impulse. In the pilot phase of the study, the median baseline blood pressure prior to stimulation of the baroreceptors was 110.8mmHg. After stimulation the median blood pressure decreased to 88 mmHg. The average decrease in blood pressure was 22.8 mmHg. This decrease of blood pressure after stimulation of the baroreceptors is statistically significant (p < 0,0001) and the proof of concept was shown. During the extended phase all three probes had a significant effect on blood pressure lowering (p <0,0001). The study confirmed that aortic baroreceptor stimulation has an effect on blood pressure lowering. This is a novel field of blood pressure manipulation The haemodynamic effects of long-term aortic baroreceptor stimulation are unknown. Further investigations need to be done to determine whether a similar effect can be induced in different species such as primates and humans. Key Words: Aortic baroreceptor stimulation; Autonomic nervous system, Carotid Baroreceptors, Hypertension, Systolic blood pressure.